1998
DOI: 10.1038/bjc.1998.63
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor beta 1 and sodium butyrate differentially modulate urokinase plasminogen activator and plasminogen activator inhibitor-1 in human breast normal and cancer cells

Abstract: Summary The effects of transforming growth factor beta 1 (TGF-i1) and sodium butyrate on cell proliferation and the urokinase plasminogen activator (uPA) system were examined in normal human breast epithelial cells (HBECs) and in a breast cancer cell line, MDA-MB-231. In HBECs, TGF-31 inhibited cell proliferation and uPA activity, while it augmented plasminogen activator inhibitor-1 (PAI-1) antigen level. Sodium butyrate inhibited both cell proliferation and uPA activity but did not affect the level of PAI-1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…As shown previously,28 linoleic acid had the greatest effect on the induction of PAI-1 in MDA-MB-231 cells, consistent with our previous observations that linoleic acid increased the expression of PAI-1 in HepG2 cells 18,19. It was also reported that butyric acid inhibited both cell proliferation and uPA activity, but had no effect on PAI-1 level in MDA-MB-231 cells,29 again suggesting that FFAs with different saturation and chain lengths show different effects on the expression of PAI-1. A concentration of 500 μ M was selected for individual FFAs because our previous studies demonstrated that this concentration of FFAs induces PAI-1 expression in HepG2 cells 18,19.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As shown previously,28 linoleic acid had the greatest effect on the induction of PAI-1 in MDA-MB-231 cells, consistent with our previous observations that linoleic acid increased the expression of PAI-1 in HepG2 cells 18,19. It was also reported that butyric acid inhibited both cell proliferation and uPA activity, but had no effect on PAI-1 level in MDA-MB-231 cells,29 again suggesting that FFAs with different saturation and chain lengths show different effects on the expression of PAI-1. A concentration of 500 μ M was selected for individual FFAs because our previous studies demonstrated that this concentration of FFAs induces PAI-1 expression in HepG2 cells 18,19.…”
Section: Discussionsupporting
confidence: 90%
“…TGF- β 1-induced PAI-1 has been reported to be associated with its stimulatory effect on invasion and metastasis of MDA-MB-231 cells 29. Incubation of endothelial cells with conditioned medium from two breast cancer cell lines (MCF7 and MDA-MB-231) also demonstrated that conditioned medium from highly invasive MDA-MB-231 cells increased the tube formation of endothelial cells, which was related to the high levels of uPA and PAI-1 secreted by MDA-MB-231 cells as compared with low levels in MCF7 cells 33.…”
Section: Discussionmentioning
confidence: 99%
“…PAI1 and IGFBP-3 are also associated to the TGF-beta receptor signaling pathway [102], an interaction which was indicated in our HS578T/NOD2 protein network (Fig 3. b), as well as their downstream signaling to the major interacting node ERK1/2, (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…As PLAU inhibitor, PAI1 is directly involved in extracellular matrix remodeling and cell adhesion [115], promoting tumor progression and metastasis in several cancers, including breast cancer [116]. Interestingly, the effects of PAI1 in breast tumor progression seems to be regulated by a non-canonical TGF-beta1 pathway [102, 117, 118]. Moreover, it has also been proposed that PAI1 may regulate cell migration independently of its role as protease inhibitor [119, 120].…”
Section: Discussionmentioning
confidence: 99%